Modernisasi Pembelajaran IPS Berbasis TPACK Di Era 4.0 Kelas Tinggi Sekolah Dasar - Inesha Audia Putri; Harinaredi (Elementary Teacher Education Program, Majalengka University, 2023)
The development of science and progress in the field of technology. This advancement in the field of technology can be used as a way to improve learning activity and the quality of learning that can be done by a teacher. To be able to realize this, a teacher needs to understand and have the ability of Technological Pedagogical Content Knowledge (TPACK). TPACK is a skill that every teacher must have in the industrial revolution 4.0 era to ensure technology and data can be used. The method used is descriptive qualitative. The data sources of this research are primary data and secondary data. Data was collected using the interview method. The purpose of this study was to determine the TPACK competence of social studies teachers in grades IV, V, and VI at SD AL-Azhar Syifa Budi Cibinong. The results showed that SD AL-Azhar Syifa Budi Cibinong has integrated technology in learning such as the preparation of teaching materials which include powerpoints and digital-based learning videos. The teacher's ability to master technology during learning can be seen through the application of TPACK. The implication in this research is the utilization of TPACK-based learning in the 4.0 era. So that it helps educators and students to understand the material easily with the use of technology.